Progression of carcinogen-induced fibrosarcomas is associated with the accumulation of naïve CD4+ T cells via blood vessels and lymphatics - Ondondo, B; Jones, E; Hindley, J; Cutting, S; Smart, K; Bridgeman, H; Matthews, K; Ladell, K; Price, D; Godkin, A; Ager, A; Gallimore, A; et al. (2014)
The tumor microenvironment comprises newly formed blood and lymphatic vessels which shape the influx, retention and departure of lymphocytes within the tumor mass. Thus, by influencing the intratumoral composition of lymphocytes, these vessels affect the manner in which the adaptive immune system responds to the tumor, either promoting or impairing effective antitumor immunity. In our study, we utilized a mouse model of carcinogen-induced fibrosarcoma to examine the composition of tumor-infiltrating lymphocytes during tumor progression. In particular, we sought to determine whether CD4 Foxp3 regulatory T cells (Tregs) became enriched during tumor progression thereby contributing to tumor-driven immunosuppression. This was not the case as the proportion of Tregs and effector CD4 T cells actually declined within the tumor owing to the unexpected accumulation of naïve T cells. However, we found no evidence for antigen-driven migration of these T cells or for their participation in an antitumor immune response. Our data support the notion that lymphocytes can enter tumors via aberrantly formed blood and lymphatic vessels. Such findings suggest that targeting both the tumor vasculature and lymphatics will alter the balance of lymphocyte subpopulations that enter the tumor mass. A consideration of this aspect of tumor immunology may be critical to the success of solid cancer immunotherapies. What's new? It is well known that a tumors' microenvironment can impair the anti-tumor immune response. The culprits are usually assumed to be various suppressor cells and cytokines. In this study, however, the authors found that seemingly innocuous, naïve T cells may also play a significant role - simply by accumulating and possibly out-competing activated effector cells within the tumor. A better understanding of the signals produced by the tumor microenvironment may allow researchers to alter this T-cell pool, thus enhancing the immune response. © 2013 The Authors. Published by Wiley Periodicals, Inc. on behalf of UICC.